Connective tissue growth factor gene expression and decline in renal function in lupus nephritis - Tachaudomdach,C. (Spandidos Publications, 2015)
In lupus nephritis (LN), kidney inflammation may be followed by fibrosis and progressive decline in function. Transforming growth factor (TGF)-β is a notable mediator of fibrosis, but it has other beneficial roles, thus indicating a need for alternate therapeutic targets for inhibition of fibrosis. Connective tissue growth factor (CTGF) acts as a downstream mediator of TGF-β in promoting fibrosis, without mediating the immunosuppressive effects of TGF-β. Animal studies show that CTGF may have important roles in renal fibrosis, but data are limited in human subjects. The present study tested the hypothesis that renal CTGF mRNA expression is related to TGF-β1 and collagen I expression and is predictive of renal function deterioration in patients with LN (n=39). Gene expression was measured using multiplex real-time quantitative RT0-PCR and renal function was estimated using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) glomerular filtration rate (GFR) equation. Decline in GFR was assessed by regression of GFR at biopsy to 1 year following biopsy. CTGF mRNA expression was significantly correlated with TGF-β1 and collagen I. GFR at biopsy was 89.2±39.2 ml/min. Renal CTGF mRNA expression correlated inversely with baseline GFR. Renal CTGF mRNA was significantly higher in patients with moderate to severe CKD compared to those in the milder CKD group (low GFR 4.92±4.34 vs. high GFR 1.52±1.94, p<0.005). CTGF mRNA was also higher in patients with subsequent decline in GFR [GFR decline (5.19±4.46) vs. no GFR decline (1.79±1.97); P<0.01]. In conclusion, renal expression of CTGF was positively related to TGF-β1 and collagen I in patients with LN. Furthermore, high CTGF mRNA expression was associated with poor GFR at baseline and subsequent deterioration of kidney function. CTGF expression in the kidney may serve as an early marker for renal disease progression and could be evaluated as a target for therapeutic intervention to prevent renal failure in LN.